Prenatal Dexamethasone Exposure Programs the Development of the Pancreas and the Secretion of Insulin in Rats - Yu-Chieh Chen; Ying-Hua Huang; Jiunn-Ming Sheen; You-Lin Tain; Hong-Ren Yu; Chih-Cheng Chen; Miao-Meng Tiao; Ho-Chang Kuo; Li-Tung Huang (Elsevier, 2017)
There is increasing epidemiological evidence indicating that many chronic diseases originate during early life, even before birth, through what are termed fetal programming effects. Prenatal glucocorticoid is frequently used clinically to accelerate the maturation of the lung, but its long-term effects remain unclear. Methods: We gave pregnant Sprague-Dawley rats either intraperitoneal dexamethasone (0.1 mg/kg body weight) or vehicle at Gestational Days 14-20 and assessed the effects to pancreas at Postnatal Days 7 and 120. Results: We found fewer pancreatic β cell fractions (0.31 ± 0.05 % vs. 0.49 ± 0.05 %, p = 0.013) and tissues (0.0017 ± 0.0002 % vs. 0.0025 ± 0.0002 %, p = 0.042) and decreased secretion of insulin in response to a glucose challenge at Postnatal Day 105 (1.00 ± 0.19 ng/mL vs. 1.57 ± 0.17 ng/mL at the 15-minute time-point, p = 0.046) in rats treated prenatally with dexamethasone. At Postnatal Day 7 in rats treated prenatally with dexamethasone, the expression of pancreatic duodenal homeobox gene-1 and V-maf avian musculoaponeurotic fibrosarcoma oncogene homolog A was lower than that in the rats in the Vehicle group (0.22 ± 0.07 vs. 1.00 ± 0.41 fold, p = 0.01, 0.20 ± 0.12 vs. 1.00 ± 0.35 fold, p = 0.01) while the histone deacetylases activity (54.2 ± 3.7 ng/h/mL vs. 37.6 ± 3.5 ng/h/mL, p = 0.012) and 8-hydroxy-2-deoxyguanosine staining (1.34 ± 0.01 vs. 1.00 ± 0.02 fold, p < 0.01) were higher. Conclusion: Prenatal dexamethasone exposure affects early postnatal gene expression related to pancreas development and may exert an effect on β-cell development at 120 postnatal days.